Slava velikomu sovetskomu narodu : sozdatel' kommunizma! - Antonov, K (Плакат СССР (Plakat), 1979)
Colour lithograph from painting; portrait of three Soviet workers representing different fields; red flag that says 'KPPP' ('USSR') waving in background Original title: Слава великому советскому народу : создатель коммунизма! PO-0134